(untitled) (Fiep Bulletin - online, 2013)
The Swimming for Persons with Special Needs Project (piracema), is na association with the University of Santa Cruz do Sul (UNISC) and Association of Parents and Friends of Exceptional (APAE). It is one of the oldest projects created by UNISC since 1984 given this service for 30 students, with the most diverse pathologies. The objective of the project is to promote activities in the water environment so that students increase their repertoire of attitudes in the water and when possible elsewhere too. This research have the objective to evaluate the motor age of the students participating in the project. Subjects of this study were 14 students of both sexes. Was implemented tests of Development Motor Scale (EDM). The studentes were evaluated as their general motor age and in each of the specific aspects of the tests: small motricity, Global motricity, Balance, Body / Speed Scheme, Space Organization and Language / Temporal Organization. It appeared that in the General Motor Age the majority of students have 4 years; About small motricity, has been evaluated that some of the students have motor age of 2 years or less; In Global motricity aspect a fraction of the students have 2 years of motor age or less; About balance half of the pupils have the motor age of 2 years or less; With regard to Psychotherapy / Speed scheme the largest percentage of students have motor age of 3 or 4 years; Space Organization’s test shows that the majority of students have motor age of 3 years; And finally, on the language / Organization Temporal a portion of students have motor age of 2 years or less and another fraction have motor age of 5 years. Therefore, the end of this study we concluded that as the physical or neurological disorders the students found several difficulties in its different aspects.